Signaling Through Nucleic Acid Sensors and Their Roles in Inflammatory Diseases - Okude, Haruna; Ori, Daisuke; Kawai, Taro (Frontiers in Immunology, 2021)
Recognition of pathogen-derived nucleic acids by pattern-recognition receptors (PRRs) is essential for eliciting antiviral immune responses by inducing the production of type I interferons (IFNs) and proinflammatory cytokines. Such responses are a prerequisite for mounting innate and pathogen-specific adaptive immune responses. However, host cells also use nucleic acids as carriers of genetic information, and the aberrant recognition of self-nucleic acids by PRRs is associated with the onset of autoimmune or autoinflammatory diseases. In this review, we describe the mechanisms of nucleic acid sensing by PRRs, including Toll-like receptors, RIG-I-like receptors, and DNA sensor molecules, and their signaling pathways as well as the disorders caused by uncontrolled or unnecessary activation of these PRRs.